2006
DOI: 10.1080/10803548.2006.11076686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diabetic Neuropathy on Body Sway and Slip Perturbation Detection in Older Population

Abstract: Postural control is a common mechanism tosway slip perturbation detection center of pressureCorrespondence and requests for offprints should be sent to Byung Joon Kim,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This survey suggests that failure to recover from a trip is a common perceived cause of falls and may indicate a delayed reactive strategy. This could be due to slowed rate of force production in weakened muscles or sensory dysfunction, as seen in other peripheral neuropathies and older people (Handsaker et al, ; Kim & Robinson, ). A study by Nardone et al () explored reactive strategies in people with peripheral neuropathy, relating them to postural control but not to falls.…”
Section: Discussionmentioning
confidence: 99%
“…This survey suggests that failure to recover from a trip is a common perceived cause of falls and may indicate a delayed reactive strategy. This could be due to slowed rate of force production in weakened muscles or sensory dysfunction, as seen in other peripheral neuropathies and older people (Handsaker et al, ; Kim & Robinson, ). A study by Nardone et al () explored reactive strategies in people with peripheral neuropathy, relating them to postural control but not to falls.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few researchers have analyzed data in ML axis 10 24 25 26 27 28 29 30 . In contrast with the other researches Kim and Robinson 28 found a significant difference in postural sway variables in diabetic neuropathy and healthy controls in AP and ML axis. Results in the present study suggest a multidirectional involvement of postural stability measures.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral instability was introduced by some studies as a marker of impaired balance in DN patients [33]. Also, alterations in the balance parameters in ML direction recorded by force platform demonstrated that DN patients are less stable in the ML direction of postural sway parameters [11] and suggested the crucial role of vestibular system in the control of hip strategy in ML direction [12].…”
Section: Discussionmentioning
confidence: 99%